Tempeh as Source of Halal Food for Thailand’s Java Mosque Congregation - Emi Erawati; Anika Candrasari; Isman; Zahiyah Wulan Supriyono; Syahrani Shabrina Dewantari; Safira Rijka Ardima; Hafizh Rakha Bintang Gutama; Dea Marta (International Journal Of Community Service, 2026)
International community servise held on Masjid Java, Bangkok Thailand. The activies following by 30 members consist of women and men Java Mosque Congregation, Muhammadiyah brand of Thailand, Ngajikok, and Indonesian Diaspora in Thailand. The activies held on 2nd June 2026. The activities consist of two part. In the first part presenter done presentation about tempeh as source halal food in Thailand. In the second session practice how to making tempeh and cooking class based on tempeh. The steps for making tempeh as much as 2 kg of soy bean soaked for 24 hours, soy bean epidermis cleaned until relatively cleaned, soy bean boiled in the water for 30 minutes. The soy bean boiled waiting until cooled. The 2 kg of soy bean added 2 coffe spons (approximately 3 g of yeast). The soy bean mixed in the tray with yeast until mixed sempurna. The soy bean packed by plastic klip or leaf. Plastic or leaf stabbed with a toothpick. The soy bean will be fermented for 48 hours in the room temperature. The soy bean fermeted layed in the floor or table with coted by paper or plastic. The international community service can impart the skills and information needed to make tempeh from soy beans. The pre-test average score rose from 57.39 to 77.39.